(untitled) (Journal of Parents and Teachers, 2014)
There are multiple intelligences that are developed to a greater or lesser extent in all people. These intelligences are largely related with the opportunities that are provided to the child during its development. Into the education and the family contexts a lot of activities can be conducted to identify what are the intelligences of the child and how to develop them. The play and experimentation activities are optimal for their development